Repercussions of agricultural land conversion policy on food security in Indonesia. Issue 3 (June 2021) - Gultom, O B; Ginting, B; Lubis, M Y; Azwar, T K D; Pasaribu, M P J
Abstract: The state guarantees sufficient food for every citizen as regulated in the 1945 Constitution of the Republic of Indonesia. Food availability is highly dependent on the existence of sustainable food agricultural lands. The conversion is the cause of food agricultural land decrease. Unmet food needs will then affect national food security. The problem in this research is the effect of granting permits for the conversion of productive agricultural land into residential land and its relation to food security in Indonesia. This legal research uses a normative juridical approach. Data was collected through a literature review and analyzed qualitatively. The results show that agricultural land is decreasing every year due to its conversion into residential and infrastructural lands for the public interest. In the end, with insufficient food needs, national food security is diminished. In conclusion, permits to convert sustainable food agricultural lands should only be given on the condition. The recommendation of this research is for the regional government, the Ministry of Agrarian and Spatial Planning/National Land Agency (ASP/NLA), and Notary/Land Deed Official to work collaboratively in providing information on the impact of agricultural land conversion on the sustainability of food availability.